2020
DOI: 10.1177/1932296820963657
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Glucose Concentrations in Frozen Plasma

Abstract: Background: Conflicting information is available regarding the stability of glucose concentrations in frozen plasma samples. Clinical trials could benefit from such long-term storage because it would allow usage of a central laboratory with higher-quality laboratory analyzers in contrast to mobile analyzers in a decentralized setting. Methods: In this study, venous blood samples were collected in lithium-heparin gel tubes. Plasma was separated immediately after blood was drawn, and from each of the 21 plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…It was previously reported that the glucose levels were stable in the stored plasma samples, and the loss of glucose was less than 1.82% in plasma frozen for a period of 3 months at −80 °C. 41 Recoveries of biomarkers in a spiked pooled serum sample ranged from 80 to 120%.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It was previously reported that the glucose levels were stable in the stored plasma samples, and the loss of glucose was less than 1.82% in plasma frozen for a period of 3 months at −80 °C. 41 Recoveries of biomarkers in a spiked pooled serum sample ranged from 80 to 120%.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%